2021
DOI: 10.3390/land10111120
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Spatiotemporal Variation of Carbon Storage Driven by Land Use Policy in the Yangtze River Delta Region

Abstract: Land use/land cover (LULC) change driven by land use policy always leads to dramatic change in carbon storage and sequestration, especially in a rapidly urbanizing region. However, few studies explored the influences of land use polices on carbon storage and sequestration in a rapidly urbanizing region. Through Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) model, the spatial-temporal pattern of carbon storage altered by LULC transformation and its linkage with land use policies were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 35 publications
(75 reference statements)
0
11
0
Order By: Relevance
“…Due to the insignificant change in water areas under the BCU scenario, the carbon sequestration benefits of water areas are not immediately apparent. This section’s findings can serve as an empirical study of land use policy-induced carbon stock changes [ 5 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the insignificant change in water areas under the BCU scenario, the carbon sequestration benefits of water areas are not immediately apparent. This section’s findings can serve as an empirical study of land use policy-induced carbon stock changes [ 5 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Land use and cover change (LUCC) influences carbon cycling by altering the spatial and temporal patterns of ecosystems, and governments have all decided to increase terrestrial ecosystem carbon stocks to offset CO 2 emissions from societal development [ 3 , 4 ]. The implementation of the action plan to address climate change has been on the agenda since China proposed, in 2020, to strive to achieve the carbon peak by 2030 and strive to complete the carbon-neutral target by 2060 [ 5 ]. Agriculture and forestry are two policy-oriented engineering techniques that have been found to increase ecosystem carbon storage.…”
Section: Introductionmentioning
confidence: 99%
“…Land use/land cover (LULC), topographic conditions, and climate change play an important role in the formation and allocation of ESs [3]. Inappropriate changes in LULC may lead to the extinction of local species and the reduction of natural habitats and ecosystem functions, thereby affecting the provision of ESs, such as carbon sequestration [4], water conservation [5], and food production [6]. As ES provision is based on the interaction of multiple related ecological processes, complex relationships usually exist among ESs, i.e., trade-offs and synergies (TOSs) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Land use change is an essential factor affecting carbon stock. Positive ecological evolution increases land carbon stocks (Meena et al, 2018;Cai et al, 2021;He et al, 2022), mainly including the conversion of cultivated land and unused land to woodland and grassland (Chuai et al, 2021;Meena et al, 2018;Xu et al, 2021;Deng et al, 2022), but also a small increase in wetlands (Hou et al, 2022;Dai et al, 2021). However, most studies have found that carbon stocks have declined over time because of land use change (Li et al, 2021;Zhu et al, 2021;Wang et al, 2022;Zhu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%